Determination of blood pressure in carriers of artificial ventricle continuous flow: Practice report (Research, Society and Development, 2023)
The objective of the research is to report the procedure for determining blood pressure in patients with continuous flow artificial ventricle. This is a descriptive, exploratory, experience report type study. The specialized and evidence-based professional practice allowed observing that the use of this procedure among patients with continuous flow artificial ventricle can be performed by the previously trained nursing team. The continuous flow pump mechanism alters the blood pressure verification mechanism, as it modifies the presence of pulsatility. The most recommended technique for this profile of patients, in a non-invasive way, is through the use of vascular Doppler to verify the mean arterial pressure. Therefore, in recent years, the use of an artificial ventricle has been on the rise as a therapeutic alternative used in our environment and requires specific care, pressure measurement being one of them and of great importance. This study allowed listing the care and guidelines for professionals and patients.